BRIDGING GAP BETWEEN ARTIFICIAL INTELLIGENCE AND MULTIPLE INTELLIGENCE- AN OVERVIEW - Sharmila Rajesh Ponnoran (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
Defining intelligence in an unorthodox manner is “what intelligence tests test?”: Normally, humans link mental testing scores i.e., IQ with intelligence which focuses primarily on logics, mathematics and over language skills. The MIT also known as Multiple Intelligence theory of 1983, proposed by Howard Gardner, a psychologist from America and Education and Cognition Professor at Harvard University, explains intelligence in a better way. The Multiple Intelligence theory proposes that various intelligence though each unique in type are in every individual who possess in variable degrees. This paper opens the opportunity to take advantages of both intelligences i.e. Multiple Intelligence & Artificial Intelligence. The paper presents a brief overview of how aspects of AI are gradually covering multiple intelligences is given below